2011
DOI: 10.1007/s10753-011-9334-4
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Pod Inhibits Inflammatory Mediator Production by Lipopolysaccharide-Stimulated RAW 264.7 Murine Macrophage Cell Lines

Abstract: Pro-inflammatory mediators produced during inflammatory response have been demonstrated to initiate and aggravate pathological development of several chronic diseases. Plant bioactive constituents have been reported to exert anti-inflammatory activities. Various parts of Moringa oleifera have long been used as habitual diets and traditional remedy along the tropical region. Anti-inflammatory activity of boiled M. oleifera pod extract was assessed by measuring pro-inflammatory mediator expression in the lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 60 publications
7
36
0
Order By: Relevance
“…An inhibitor of NF-κB (IκB) protein, which is the target for anti-inflammatory drug development [37], are principally supposed to inhibit p65-containing complex of NF-κB with noticeably high affinity [38]. Some reports have suggested that MO inhibits kinases upstream of NF-κB, IKB kinase and the MAP kinases [39], which are induced by oxidative stress. This would be consistent with our finding that basal activity was not affected, only that induced by LPS and CSE.…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitor of NF-κB (IκB) protein, which is the target for anti-inflammatory drug development [37], are principally supposed to inhibit p65-containing complex of NF-κB with noticeably high affinity [38]. Some reports have suggested that MO inhibits kinases upstream of NF-κB, IKB kinase and the MAP kinases [39], which are induced by oxidative stress. This would be consistent with our finding that basal activity was not affected, only that induced by LPS and CSE.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol extract from M. oleifera seeds has also shown anti-inflammatory activity against ovalbumin-induced respiratory tract inflammation in guinea pigs (Mahajan and Mehta, 2007). Bioactive compounds in M. oleifera pods can contribute to anti-inflammatory activity to improve the pathogenesis of chronic inflammatory diseases (Muangnoi et al, 2012).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…This is an established fact that leaf, fruit, seed, and root extracts have been used since long back in enhancement of inflammation related disorders, for example, asthma, allergic rhinitis, atopic dermatitis, and rheumatoid arthritis (Chumark et al, ; Hamza, ; Lee et al, ; Muangnoi, Chingsuwanrote, Praengamthanachoti, Svasti, & Tuntipopipat, ). Anti‐inflammatory activities are possibly attributed due to the presence of 4‐[(α‐Lrhamnosyloxy) benzyl] isothiocyanate, 4‐[(4′‐O‐acetyl‐α‐ l ‐rhamnosyloxy) benzyl]isothiocyanate (Stohs & Hartman, ), quercetin, quercetin‐3‐O‐glucoside, kaempferol glucosides, (Coppin et al, ), 4‐(2‐O‐acetyl‐ α‐ l ‐rhamnosyloxy)benzyl isothiocyanate, 4‐(3‐O‐acetyl‐α‐rhamnosyloxy)benzyl isothiocyanate (Cheenpracha et al, ), 3,5‐dihydroxy‐6‐methyl‐2,3‐dihydro‐4H‐pyran‐4‐1, 9‐octadecenamide (Inbathamizh & Padmini, ), crypto chlorogenic acid (Vongsak, Gritsanapan, Wongkrajang, & Jantan, ), aurantiamide acetate, 1,3‐dibenzyl urea (Maheshwari, Yadav, Malhotra, Dhawan, & Mohan, ; Pandey et al, ) and 4(α‐ l ‐rhamnosyloxy)‐benzyl glucosinolate (Galuppo et al, ).…”
Section: Resultsmentioning
confidence: 99%